Family Business Control, Strategy Selection And Strategic Performance Measurement Usage - Antonius Singgih Setiawan; Agustinus Widyartono; Johan Gunady Ony (Jurnal Akuntansi, 2021)
Firms that are managed by family businesses have developed and have an impact on the growth of a country's economy. The family business has been a concern in much of the research literature. The development of family businesses also has an interesting phenomenon related to business governance systems, especially in management control systems. Therefore, this study aims to examine the effect of the owner's role in the management of the family business, and the strategy selection on to use of strategic performance measurement on the family business. The research was conducted using quantitative methods primary data through a survey of micro, small and medium entrepreneurs in the city of Palembang. A total of 150 questionnaires were distributed to entrepreneurs. The number of questionnaires used in this study was 107 (71%). ANOVA analysis was used to test the hypothesis. The results showed that the role of the owner in controlling the family business and the strategy selection affected the strategic performance measurement.